Why is Inflation so Low after Large Devaluations? - Ariel Burstein; Martin Eichenbaum; Sergio Rebelo (Hungarian Academy of Sciences, Institute of Economics, 2003)
This paper studies the behavior of inflationnafter nine large post-1990 contractionary devaluations. A salient feature of the data is that inflation is low relative to the rate of devaluation. We argue that distribution costs and substitution away from imports to lower quality local goods can account quantitatively for the post-devaluation behavior of prices.
Keywords: F31; 330; inflation; devaluation; exchange rates